Association between hospital emergency visits for asthma and air pollution in Valencia, Spain. Issue 8 (August 1998) - Tenías, J M; Ballester, F; Rivera, M L
Abstract : OBJECTIVE: To assess the short term effect of concentrations of black smoke, sulphur dioxide (SO2), nitrogen dioxide (NO2) and ozone (O3) in ambient air on emergency room visits for asthma in the city of Valencia, Spain during the period 1994-5. METHODS: Ecological study with time series data and application of Poisson regression. Associations between number of daily emergency visits in a city's hospital and concentrations of air pollutants were analysed taking into account potential confounding factors by the standardised protocol of the air pollution and health: a European approach (APHEA) project. RESULTS: Mean (range) daily number of emergency room visits for asthma was 1 (0-5). Concentrations of all pollutants studied remained within current air quality standards. The association between an increase of 10 micrograms/m3 in ambient air pollution and asthma, measured as a relative risk (RR) of emergency visits, was significant for NO2 24 hour mean (lag 0, RR 1.076, 95% confidence interval (95% CI) 1.020 to 1.134), NO2 hour maximum (lag 0, RR 1.037, 95% CI 1.008 to 1.066), and O3 hour maximum (lag 1, RR 1.063, CI 95% 1.014 to 1.114). The association was not significant for SO2 or for black smoke during the period analysed. The effects were not significantly different for the time of year, cold months (November to April), or warm months (May to October). CONCLUSIONS: Current concentrations of ambient air pollution in Valencia are significantly associated with emergency room visits for asthma. This association is high and more consistent for NO2 and O3 than for particulate matter and SO2 (classic pollutants).